State-Dependent Phillips Curve - Hyun Hak Kim; Na Kyeong Lee (Economies)
We propose a state-dependent Phillips curve (PC) where the regime has changed endogenously. Using this framework, a free-standing PC is constructed. This study tests the robustness of the model, various types of inflation, slack measures, and various expectation measures. The PC is found to work strongly during recessionary periods but becomes weaker once an economy recovers. The latent factors that determine the regimes are highly correlated with the uncertainty measure. During recessionary periods, the uncertainty becomes negatively more certain and strengthens the relationship between inflation and labor market slack.